PROSES MINING UNTUK OPTIMASI PROSES BISNIS - Nur Fitrianti Fahrudin (Jurnal Ilmiah Teknologi Infomasi Terapan, 2020)
Organizations currently need to conduct an analysis of their business processes in order to improve business performance and productivity. In addition, this analysis can be a way to compete with competitors. However, the analysis of this business process if done manually requires considerable time. Process mining is a technique that helps solve this problem. Information systems that are owned by a company certainly store their every business activity. This data can be processed to find business processes that occur. This data is usually called an event log. Event logs help organizations to find gaps between business processes that occur with those expected. Based on this gap business processes can later be evaluated for later improvement.